A MULTI-CRITERIA DECISION-MAKING BASED COURSE ASSESSMENT FRAMEWORK: DEVELOPMENT AND APPLICATION - Aburas, Hani Mohammad; Batarfi, Ibraheem; Bahshwan, Abdullah; Alzahrani, Adam; Qarout, Abdullah (The South African Journal of Industrial Engineering, 2022)
Evaluation of the educational process is essential to its development and improvement. This paper aims to create a model for evaluating students’ satisfaction with industrial engineering courses using Multi-Criteria Decision-Making (MCDM) tools. The research began with a course evaluation data survey with 28 questions (variables). Then the assessment model was proposed, based on the previously collected data. The suggested assessment model identified the constructs using exploratory factor analysis (EFA). Then the extracted variables and the resulting constructs were prioritised using the analytic hierarchy process (AHP). Next, a structured local questionnaire was drawn up and distributed to industrial engineering students at a Saudi university to validate the developed model. After that, the suggested framework was applied to the data to assess the students’ overall satisfaction with the course. Finally, it was found that the Operations Research Track, of the five current tracks, scored the highest satisfaction rate. This study’s results could be helpful in knowing the importance of MCDM in the evaluation process, as it distinguishes the value of students’ evaluations for the development and growth of the evaluation of educational courses.